2015
DOI: 10.1111/jai.12802
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of female cardinalfish, Epigonus crassicaudus de Buen, 1959

Abstract: Summary The cardinalfish (Epigonus crassicaudus) is a long‐lived and endemic deep‐water fish inhabiting the central and southern coast off Chile. Knowledge about basic biological attributes including maturity aspects is fragmentary in this species. The historical and comprehensive data available are applied to provide a detailed study of the reproductive biology of the female cardinalfish. The gonadosomatic index was computed from 5110 female gonads collected by onboard scientific observers between October 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…If L∞ = 34 cm FL, indicated by Moyano et al (2018), is considered, the value for this relationship in E. crassicaudus would be 0.65-0.67. The results for L50% confirmed those reported by Flores et al (2015), who used the histologic methodology to estimate this value, could validate the macroscopic approach in fish maturity studies when funding is scarce, or a quick estimation is needed.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…If L∞ = 34 cm FL, indicated by Moyano et al (2018), is considered, the value for this relationship in E. crassicaudus would be 0.65-0.67. The results for L50% confirmed those reported by Flores et al (2015), who used the histologic methodology to estimate this value, could validate the macroscopic approach in fish maturity studies when funding is scarce, or a quick estimation is needed.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, after 28 cm FL, some portion of females continued being assigned to the immature fraction of the population, which is frequent in macroscopic scales of maturity because mature adult females in resting, could be mistakenly classified as immature due to its poor ovarian development (Hunter & Macewicz, 2003;Murua & Saborido-Rey, 2003;Tomkiewicz et al, 2003;Brown-Peterson et al, 2011). Despite this apparent bias in the allocation of maturity states, L50% reached 22.3 cm FL close to the value estimated by Flores et al (2015), who reported an L50% of 23.2 cm FL for samples coming from a similar study area. Compared with L50% in technical reports, our results were close to 24.3 cm FL estimated by Gálvez et al (2013) and smaller than 32.1 cm FL, estimated by Cubillos et al (2009), who considers smaller samples and a more restricted study area.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations